Collaborative Planning Method for Flexibility Supply and Demand in Distribution Networks Considering Flexible Resource Transmission - XU Jiayu, WANG Fangmin, LI Bing, GU Jingda, LIU Shuai, TONG Xiaoning, ZANG Tianlei (Dianli jianshe)
[Objective] To address the insufficient flexibility caused by the large-scale integration of renewable energy into distribution networks and enhance their renewable energy accommodation capacity， this paper proposes a flexibility supply-demand collaborative planning method for distribution networks considering flexibility resource transmission characteristics. [Methods] The proposed method uses distribution network nodes as analytical entities to establish a flexible supply-demand model and a network transmission flexibility resource model. In addition， we developed a two-layer collaborative planning model incorporating the resource transmission characteristics. The upper-layer model aims to maximize the wind/PV integration capacity and minimize comprehensive costs through the coordinated planning of distributed generation， network topology， and energy storage configuration. The lower-layer model optimizes the operational costs through operational optimization. The two-layer model is converted into a single-layer model for the solution via the KKT conditions， ultimately obtaining planning results that satisfy the flexibility requirements of the distribution network. [Results] Simulation results based on a modified IEEE 33-node system demonstrate that， while considering flexibility transmission constraints slightly increases operational costs， the total planning cost decreases by 10%. Under the proposed collaborative planning strategy， as branch transmission margins gradually decrease， the distribution network achieves spatiotemporal matching of flexible supply and demand by significantly increasing the flexible resource dispatch frequency. [Conclusions] The proposed flexibility planning model enhances both renewable energy accommodation capacity and flexible resource regulation capability in distribution networks. A detailed consideration of various costs in the planning and operational stages improves network flexibility while maintaining economic feasibility and meeting distribution network planning requirements. Compared with conventional flexibility planning schemes， this approach effectively avoids the transmission congestion issues encountered in practical operations.